Feasibility of Using Bimetallic Plasmonic Nanostructures to Enhance the Intrinsic Emission of Biomolecules - Chowdhury, Mustafa H. (2011)
Detection of the intrinsic fluorescence from proteins is important in bio-assays because it can potentially eliminate the labeling of external fluorophores to proteins. This is advantageous because using external fluorescent labels to tag biomolecules requires chemical modification and additional incubation and washing steps which can potentially perturb the native functionality of the biomolecules. Hence the external labeling steps add expense and complexity to bio-assays. In this paper, we investigate for the first time the feasibility of using bimetallic nanostructures made of silver (Ag) and aluminum (Al) to implement the metal enhanced fluorescence (MEF) phenomenon for enhancing the intrinsic emission of biomolecules in the ultra-violet (UV) spectral region. Fluorescence intensities and lifetimes of a tryptophan analogue N-acetyl-L-tryptophanamide (NATA) and a tyrosine analogue N-acetyl-L-tyrosinamide (NATA-tyr) were measured. Increase in fluorescence intensities of upto 10-fold and concurrent decrease in lifetimes for the amino acids were recorded in the presence of the bimetallic nanostructures when compared to quartz controls. We performed a model protein assay involving biotinylated bovine serum albumin (bt-BSA) and streptavidin on the bimetallic nanostructured substrate to investigate the distance dependent effects on the extent of MEF from the bimetallic nanostructures and found a maximum enhancement of over 15-fold for two layers of bt-BSA and streptavidin. We also used finite difference time domain (FDTD) calculations to explore how bimetallic nanostructures interact with plane waves and excited state fluorophores in the UV region and demonstrate that the bimetallic substrates are an effective platform for enhancing the intrinsic emission of proteins and other biomolecules.